The value of shared corporate services in improving patient care - Nompozolo, Nikiwe Nomapelo (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
This case study was undertaken from mid 2003 to December 2005. It investigates the influence of the Corporate Services Centre (CSC) on customer (patient) service quality in the East London Hospital Complex (ELHC). This approach was justified on the basis that even though most patients do not have enough knowledge of clinical practices in order to make an accurate assessment on their quality, the same patients would readily appreciate factors such as faster turnaround times, drug availability and cleanliness. The study focuses on both service providers and end users for a quality health service delivery by looking at the potential of the shared corporate services centre. This was done by identifying important areas for improvements, such as response times, waiting periods and other aspects of the various services. The ELHC was formed from the merger of Frere and Cecilia Makiwane Hospitals, with a distance of 26km between the two institutions. The complex itself was in its infancy stages, having had to go through a process of re-engineering, rationalisation and standardisation of the two hospitals. The study seeks to answer the following key question: What has been the contribution of the corporate service centres in relation to health care service quality? The study examines the impediments to the realization of full potential of the Corporate Services Centre (CSC) through expedited decision-making and improved turnaround times. The main functions of the CSC were Procurement and Asset Management; General Administration (including but not limited to Transport, Office equipment, Patient Administration, Office Support, and Professional Secretariat Support); Financial Management and Administration; and Human Resource Management and Human Resources Administration. The study recommends that the CSC, to justify its existence, needs to consult with the clinicians and the patients to better understand what their needs and aspirations are. The study also emphasizes that the CSC is there purely to remove the administrative load and ease the processes and the biggest mistake is to make it an authority over the hospital, instead of being a support. Finally, it was realized that a lot of structural changes, business processes and organisational cultural changes are essential if one wants to create an impact through shared corporate services.
Keywords: East London Hospital Complex; Hospital care -- Quality control -- South Africa -- East London -- Case studies; Customer services -- Quality control -- South Africa -- East London -- Case studies; Customer services -- Rating of -- South Africa -- East London; Hospital care -- Evaluation -- South Africa -- East London